The effect of the marketing mix on customer relationship management - an exploratory study of the opinions of a sample at Nasr General Company for Mechanical Industries - Baghdad - Amer Abdul Latif Kazem Al Ameri,; Ali Khalifa Ahmed al - Mashhadani, (Iraqi Journal for Administrative Sciences, 2025)
The research dealt with both variables of the marketing mix and customer relationship management. The first independent variable included (the marketing mix has four dimensions that include product, pricing, promotion, and distribution. The other dependent variable, customer relationship management, included three dimensions that include customer satisfaction, customer loyalty, and customer value) . The research problem included several questions, including: What is the reality of using the marketing mix in the researched company, and what are the researched company’s approaches to the philosophy of customer relationship management? The objectives of the research were identified by identifying the reality of the marketing mix in the researched company, and introducing the concept of customer relationship management for the researched company, which enables it to achieve continuity in the market and increase its profits. The research included two main hypotheses, the first was that there is a significant correlation between the marketing mix and customer relationship management, and the other was (there is a significant impact of the marketing mix on customer relationship management). The research was conducted on the directors, heads of departments and certificate holders of the Nasr General Company for Mechanical Industries - Baghdad, who numbered (777) workers, and (94) questionnaire forms were distributed to the research sample as the tool that the research adopted to collect data and information, in addition to the interviews that the researchers conducted with part of the sample, which It resulted in results that expressed the reality of the researched company, and a number of statistical methods were used to process the data, including: (arithmetical mean, percentages, and standard deviation for the purpose of describing the sample, the simple linear correlation coefficient Spearman) to test the validity of the correlation hypotheses, and simple linear regression to test the validity of the effect. The research came out with several conclusions, the most important of which were: The results showed a strong, significant, and positive correlation between the main variables of the research (the marketing mix and customer relationship management), which indicates the benefit of the marketing mix in enhancing and improving customer relationship management. Finally, the research reached several recommendations The most important of which is: working to deepen the concept of customer relationship management and making it part of the system and fabric of the organizational culture of the researched company, as it ensures its vision and strategic mission that it achieves financial profits for the company, improves its reputation with customers, and increases its resistance to competing companies upon application.